2021
DOI: 10.33647/2713-0428-17-3e-99-105
|View full text |Cite
|
Sign up to set email alerts
|

Directed regulation of the human microbiome: contribution to the solution of the demographic problem in Russia

Abstract: In order to solve the demographic problem that has arisen in Russia, comprehensive multilateral approaches are required, aimed at increasing the birth rate and reducing child and adult mortality. One approach to solve this problem is directed regulation of the human microbiome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…aeruginosa 27853) to Caco-2 cells was inhibited in a dose-dependent manner by the addition of Slp2 in the medium. At the same time, Caco-2 cultivated in the presence of Slp2 increased the adhesion of Bifidobacterium longum subspecies infantis BLI 2780 to the enterocytes of these line[24].…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…aeruginosa 27853) to Caco-2 cells was inhibited in a dose-dependent manner by the addition of Slp2 in the medium. At the same time, Caco-2 cultivated in the presence of Slp2 increased the adhesion of Bifidobacterium longum subspecies infantis BLI 2780 to the enterocytes of these line[24].…”
mentioning
confidence: 83%
“…We found that Slp2 increases the activity of intestinal ALP (Figure 3A) in Caco-2 enterocytes and inhibits the adhesion of NEC-inducing pathogens to these intestinal cells (Table 2). At the same time, Slp2 stimulates the adhesion of bifidobacteria on Caco-2 enterocytes, ensuring the formation of normal parietal microflora of the newborns [24]. Therefore, this could be a mechanism behind the bifidobacteria correlation with Slp2 and ALP activities.…”
Section: Cell Differentiation Of Caco-2 Cells Treated With Slp2mentioning
confidence: 97%
See 3 more Smart Citations